Morphology, songs and genetics identify two new cicada species from Morocco: Tettigettalna afroamissa sp. nov. and Berberigetta dimelodica gen. nov. & sp. nov. (Hemiptera: Cicadettini) - Costa, Gonçalo João; Nunes, Vera L.; Marabuto, Eduardo; Mendes, Raquel; Laurentino, Telma G.; Quartau, José Alberto; Paulo, Octávio S.; Simões, Paula Cristina (Zootaxa, 2017)
Morocco has been the subject of very few expeditions on the last century with the objective of studying small cicadas. In the summer of 2014 an expedition was carried out to Morocco to update our knowledge with acoustic recordings and genetic data of these poorly known species. We describe here two new small-sized cicadas that could not be directly assigned to any species of North African cicadas: Tettigettalna afroamissa sp. nov. and Berberigetta dimelodica gen. nov. & sp. nov. In respect to T. afroamissa it is the first species of the genus to be found outside Europe and we frame this taxon within the evolutionary history of the genus. Acoustic analysis of this species allows us to confidently separate T. afroamissa from its congeners. With B. dimelodica, a small species showing a remarkable calling song characterized by an abrupt frequency modulation, a new genus had to be erected. Bayesian inference and maximum likelihood phylogenetic analyses with DNA-barcode sequences of Cytochrome C Oxidase 1 support the monophyly of both species, their distinctness and revealed genetic structure within B. dimelodica. Alongside the descriptions we also provide GPS coordinates of collection points, distributions and habitat preferences.